Absolute Lymphocyte Count and its Correlation with Serum Ferritin Level: An early indicator of disease severity in COVID-19 - Sehar Khaliq , Kiran Fatima Farooq , Wajid Hussain ,Sami Saeed (Journal of Rawalpindi Medical College, 2021)
Introduction: The massive number of cases with SARS-Cov-2 has put a tremendous pressure on healthcare systems all over the world. Most of the countries have declared health emergency. In these highly challenging times and also to reduce the risk of morbidity early warning signs may be helpful.6 Objective: To correlate lymphocyte count with serum ferritin levels in patients with COVID-19 admitted in the intensive care unit of a tertiary care hospital. Material and Methods: This cross-sectional study was carried out at Fauji Foundation Hospital Rawalpindi from July 2020-December 2020. A positive COVID-19 patient was the one who had a positive real time polymerase chain reaction (PCR) for SARS-CoV-2 by sampling through nasopharyngeal swabs. 3 ml of blood is taken for Blood CP in ethylene diamine tetra acetic acid containing vacutainers and was run on Sysmex-XN series. For serum ferritin 4 ml clotted blood was collected in plain test tube. Serum ferritin was performed on AXSYM system by immunoassay using AXSYM Ferritin reagent kit pack. Covid -19 disease severity classification proposed by WHO was used to categorise the patients. (WHO COVID 19 interim guidelines). 11 Results: A total of 91 patients diagnosed with covid-19 by RT-PCR testing admitted in intensive care units (severe and critical disease) were included in the study. Out of these 91 patients ;41 were males and 50 patients were females. Mean age of the patients was 61+/- 9 years. The age range was (28-75) years. The median nadir lymphocyte count was 0.2 X 10 9/L. Mean lymphocyte count was 1.1 +/- 0.2 SD. Mean Ferritin value was 1148.5 +/- 60 SD. The Pearson correlation coefficient showed an r value of -0.60 which shows a moderate negative correlation. Conclusion: There is a significant negative correlation between lymphocyte count and serum ferritin levels